The Effect of Molasses Addition on Physical and Chemical Quality of Corn Plant Silage Given Fermented Mother Liquor - Nidia Yulanda; Nove Hidajati; Agung Budianto Achmad; Dony Chrismanto (Journal of Applied Veterinary Science And Technology, 2021)
Background: Making silage added with additives can improve the quality of silage nutrition and speed up the fermentation process. Molasses are widely used by farmers as additives for making silage. The use of molasses can be replaced with Fermented Mother Liquor (FML) in making silage. Purpose: to determine the effect of molasses addition on physical and chemical quality of corn plant silage given Fermented Mother Liquor (FML). Method: Observative data collection by making direct observations on making silage with two treatments consist of P0 (Corn Plant + 2% Fermented Mother Liquor (FML)) and P1 (Corn Plant + 2% Fermented Mother Liquor (FML) + 2% Molasses). The silage storage time was one week and on the seventh day observations were made on the physical and chemical quality of silage in each treatment. Result: The corn plant silage given fermented mother liquor (FML) without the addition of molasses produced better physical and chemical quality compared to corn plant silage given Fermented Mother Liquor (FML) with the addition of molasses. Conclusion: the corn plant silage given Fermented Mother Liquor (FML) only had better physical and chemical quality